10th IEEE International Conference on Nanotechnology 2010
DOI: 10.1109/nano.2010.5697835
|View full text |Cite
|
Sign up to set email alerts
|

Force modulation for improved conductive-mode atomic force microscopy

Abstract: We present an improved conductive-mode atomic force microscopy (C-AFM) method by modulating the applied loading force on the tip. Unreliable electrical contact and tip wear are the primary challenges for electrical characterization at the nanometer scale. The experiments show that force modulation reduces tip wear by a factor of three and enhances electrical contact between tip and sample, which allows operation at lower loading force and further reduction of tip and sample wear. Long-term wear experiments wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Force-modulation schemes are shown to be beneficial for the endurance of conductive probes. Moreover, it has been demonstrated that when using force modulation lower, load forces are needed to obtain a good electrical tip-medium contact 73,74 . Given the severe limitations in writing amorphous regions in phase-change materials, the prospects for probe-based phase-change storage are dim.…”
Section: Endurancementioning
confidence: 99%

Probe-based data storage

Koelmans,
Engelen,
Abelmann
2015
Preprint
Self Cite
“…Force-modulation schemes are shown to be beneficial for the endurance of conductive probes. Moreover, it has been demonstrated that when using force modulation lower, load forces are needed to obtain a good electrical tip-medium contact 73,74 . Given the severe limitations in writing amorphous regions in phase-change materials, the prospects for probe-based phase-change storage are dim.…”
Section: Endurancementioning
confidence: 99%

Probe-based data storage

Koelmans,
Engelen,
Abelmann
2015
Preprint
Self Cite
“…A similar technique was used to image delicate polymer surfaces and was shown to completely suppress the formation of the ripple wear patterns that are commonly observed when imaging these surfaces in contact-mode atomic force microscopy (AFM) [26]. More recently force modulation has also been shown to improve the electrical contact quality in conductive-mode AFM [27].…”
Section: Dynamic-mode Operationmentioning
confidence: 99%
“…In this paper we present a complementary strategy, a normal force modulation technique, to increase the reliability of nanoscale electrical contact and to reduce tip wear in conductive-mode SPM. The essential idea behind the proposed force modulation technique is to modulate the normal load force while the tip is in contact with the sample [20]. This modulation is achieved by actuating the cantilever at specific mechanical resonant frequencies which correspond to the normal modes of vibration.…”
Section: Introductionmentioning
confidence: 99%